Tat-CIRP Peptide Facilitates Frozen Wound Healing by Ameliorating Inflammation and Promoting Angiogenesis - Li J; Ding J; Wu H; Lu C; Wu J; Luo Q (Dove Medical Press, 2024)
Jiayan Li,1,* Jie Ding,1,* Haoyang Wu,1 Chenyan Lu,1 Jian Wu,2 Qianqian Luo1 1Department of Hypoxic Biomedicine, Institute of Special Environmental Medicine and Coinnovation Center of Neuroregeneration, Nantong University, Nantong, 226019, People's Republic of China; 2Department of Pharmacy, Huashan Hospital, Fudan University, Shanghai, 200040, People's Republic of China*These authors contributed equally to this workCorrespondence: Jian Wu, Department of Pharmacy, Huashan Hospital, Fudan University, 12 Middle Urumqi Road, Shanghai, 200040, People's Republic of China, Tel +86-21-54601295, Email jianwu12@fudan.edu.cn Qianqian Luo, Department of Hypoxic Biomedicine, Institute of Special Environmental Medicine and Coinnovation Center of Neuroregeneration, Nantong University, 9 Seyuan Road, Chongchuan District, Nantong, Jiangsu, 226019, People's Republic of China, Tel +86-513-85503378, Email qianqianluo@ntu.edu.cnBackground: Frostbite is a chemia resulting from cold-induced skin damage. The process of frostbite is often accompanied by inflammation, and the therapeutic strategies focusing on anti-inflammation are the main direction to data. Tat-CIRP is a 15 amino acid peptide containing HIV protein and cold-inducible RNA-binding protein (CIRP), which is believed to compete with endogenous CIRP for myeloid differentiation 2 (MD2) binding. This study aims to investigate the efficacy of Tat-CIRP in the treatment of frostbite.Methods: A mouse model of frostbite was established, and on the first day after frostbite occurrence, Tat-CIRP peptide was administered intravenously via the tail with a dosage interval of one day for a total of three doses. Frozen mouse skin sections were subjected to histological analysis, including hematoxylin-eosin (HE) staining, Masson staining, and immunohistochemical examination. Western blotting was performed to detect the expression level of Ki-67 in mouse skin tissue.Results: One day after frostbite, mice exhibited skin swelling and a solid appearance. From day 1 to 5 after frostbite, MD2 expression was significantly upregulated, while CIRP expression was downregulated. Compared to the frostbite group, mice treated with Tat-CIRP showed accelerated frostbite recovery, reduced levels of inflammatory factors and MD2. Furthermore, the expression of cell proliferation-associated protein Ki-67 and angiogenesis-related protein CD31 was upregulated.Conclusion: Tat-CIRP promotes frozen wound healing via inhibiting inflammation and promoting angiogenesis in frostbitten mice.Keywords: frostbite, Tat-CIRP, inflammation, angiogenesis